An update on environment-induced pulmonary edema: “When the lungs leak under water and in thin air” - Tetzlaff, Kay; Swenson, Erik R.; Bärtsch, Peter (Frontiers in physiology, 2022)
Acute pulmonary edema is a serious condition that may occur as a result of increased hydrostatic forces within the lung microvasculature or increased microvascular permeability. Heart failure or other cardiac or renal disease are common causes of cardiogenic pulmonary edema. However, pulmonary edema may even occur in young and healthy individuals when exposed to extreme environments, such as immersion in water or at high altitude. Immersion pulmonary edema (IPE) and high-altitude pulmonary edema (HAPE) share some morphological and clinical characteristics; however, their underlying mechanisms may be different. An emerging understanding of IPE indicates that an increase in pulmonary artery and capillary pressures caused by substantial redistribution of venous blood from the extremities to the chest, in combination with stimuli aggravating the effects of water immersion, such as exercise and cold temperature, play an important role, distinct from hypoxia-induced vasoconstriction in high altitude pulmonary edema. This review aims at a current perspective on both IPE and HAPE, providing a comparative view of clinical presentation and pathophysiology. A particular emphasis will be on recent advances in understanding of the pathophysiology and occurrence of IPE with a future perspective on remaining research needs.